Sex-Dependent Prescription Patterns and Clinical Outcomes Associated With the Use of Two Oral Cannabis Formulations in the Multimodal Management of Chronic Pain Patients in Colombia - Moreno-Sanz, Guillermo; Madiedo, Alvaro; Hernandez, Paula; Kratz, Janosch; Aizpurua-Olaizola, Oier; Brown, Matthew R. D.; López, Juan R.; Patiño, Jorge; Mendivelso, Fredy O. (Frontiers in Pain Research, 2022)
To date, the therapeutic us of cannabinoids in chronic pain management remains controversial owing to the limited clinical evidence found in randomized clinical trials (RCTs), the heterogeneous nature of the clinical indication, and the broad range of cannabis-based medicinal products (CBMPs) used in both experimental and observational clinical studies. Here we evaluate patient-reported clinical outcomes (PROMS) in a cohort of adult patients, diagnosed with chronic pain of diverse etiology, who received adjuvant treatment with oral, cannabis-based, magistral formulations between May and September 2021 at the Latin American Institute of Neurology and Nervous System (ILANS-Zerenia) in Bogotá, Colombia. During this period, 2112 patients completed a PROMS questionnaire aimed at capturing the degree of clinical improvement of their primary symptom and any potential side effects. Most participants were female (76.1%) with an average age of 58.7 years old, and 92.5% (1955 patients) reported some improvement in their primary symptom (p<0.001). Two monovarietal, full-spectrum, cannabis formulations containing either cannabidiol (CBD 30 mg/mL; THC < 2 mg/mL) or a balanced composition (THC 12 mg/mL; CBD 14 mg/mL) accounted for more than 99% of all prescriptions (59.5% and 39.8%, respectively). The degree of improvement was similar between both formulations, although males reported less effectiveness in the first four weeks of treatment. Sex-specific differences were also found in prescription patterns, with male patients increasing the intake of the balanced chemotype overtime. For many patients (71.7%) there were no adverse side effects associated to the treatment and those most reported were mild, such as somnolence (13.0%), dizziness (8.1%) and dry mouth (4.2%), which also seemed to fade overtime. Our results constitute the first real-world evidence on the clinical use of medicinal cannabis in Colombia and suggest that cannabis-based oral magistral formulations represent a safe and efficacious adjuvant therapeutic option in the management of chronic pain.